Effect of magnesium and zinc supplementation in the patients of essential hypertension - Singh, Suresh Kumar; Verma, Narsingh; Singh, Shraddha; Patel, M. L.; Mittal, Anupam (International Journal of Research in Medical Sciences, 2024)
Background: Primary hypertension is the most common (almost 95%) and it can easily be controlled through lifestyle modification by regular exercise and controlled diet plan. Magnesium and zinc supplementation can alleviate essential hypertension. Methods: 73 hypertensive patients were recruited. Thrice in a row with interval of 5 minutes, twice a day for 7 days high BP monitoring was done and ensured daily intake of Mg (300 mg) and Zn (10 mg) for 4 weeks. Thereafter again 4th week home Blood pressure monitoring was done. Study was done from 25 April 2023 to 24 April 2024. Secondary hypertension was excluded after proper radiological and pathological investigations. Results: Decrease in SBP by 6.9 mmHg, pre SBP 141±11.3 SD and post SBP 134±9.6 SD and DBP by 4.8 mmHg, pre DBP 91±7.8SD and Post DBP 86±73, observed after 4 weeks supplementation. In 30 medicated patients, antihypertensive showed decrease in SBP by 4.6 mmHg, pre SBP 137±11.5 SD and post SBP 132±9.6 SD with and DBP by 4.7 mmHg, Pre DBP 89.6±9.2SD and post DBP 84.9±8.7. Whereas, in a group of 43, without any medicine exhibited decline in SBP by 8 mmHg (Pre SBP 144±10 SD and Post SBP 136±9.5 and DBP by 5 mmHg, pre DBP 92±6.8 SD and post DBP 87±0.6.3 SD. Value of p<0.001 in the study group. Conclusions: Supplementation reduced blood pressure in all pre and post groups. The effect of supplementation had slighter edge on who were not taking antihypertensive medicine than were taking single medication or combined therapy.